OClO as observed by TROPOMI: a comparison with meteorological parameters and PSC observations - Pukite, J.; Borger, C.; Dörner, S.; Gu, M.; Wagner, T. (2021)
Chlorine dioxide (OClO) is a by-product of the ozone depleting halogen chemistry in the stratosphere. Although being rapidly photolysed at low solar zenith angles (SZAs) it plays an important role as an indicator of the chlorine activation in polar regions during polar winter and spring at twilight conditions because of the nearly linear dependence of its formation to chlorine oxide (ClO). Here we compare slant column densities (SCDs) of chlorine dioxide (OClO) retrieved by means of differential optical absorption spectroscopy (DOAS) from spectra measured by the TROPOspheric Monitoring Instrument (TROPOMI) with meteorological data for both Antarctic and Arctic regions for the first three winters in each of the hemispheres (November 2017–October 2020). TROPOMI, a UV-VIS-NIR-SWIR instrument on board of the Sentinel-5P satellite monitors the Earth’s atmosphere in a near polar orbit at an unprecedented spatial resolution and signal to noise ratio and provides daily global coverage at the equator and thus even more frequent observations at polar regions. The observed OClO SCDs are generally well correlated with the meteorological conditions in the polar winter stratosphere: e.g. the chlorine activation signal appears as a sharp gradient in the time series of the OClO SCDs once the temperature drops to values well below the Nitric Acid Trihydrate (NAT) existence temperature TNAT. Also a relation of enhanced OClO values at lee sides of mountains can be observed at the beginning of the winters indicating a possible effect of occurring lee waves on chlorine activation. The dataset is also compared with CALIPSO Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) polar stratospheric cloud (PSC) observations. In general, OClO SCDs coincide well with CALIOP measurements for which PSCs are detected. Very high OClO levels are observed for the northern hemispheric winter 2019/2020 with an extraordinarly long period with a stable polar vortex being even close to the values found for Southern Hemispheric winters. Also the ...